Polymer composition assessment suggests prevalence of single-use plastics among items ingested by loggerhead sea turtles in the western mediterranean sub-region. (1st January 2022) - Camedda, Andrea; Matiddi, Marco; Vianello, Alvise; Coppa, Stefania; Bianchi, Jessica; Silvestri, Cecilia; Palazzo, Luca; Massaro, Giorgio; Atzori, Fabrizio; Ruiu, Angelo; Piermarini, Raffaella; Cocumelli, Cristiano; et al.
Abstract: The ingestion of plastic is becoming a major concern for various species and particularly for marine turtles across the globe. The loggerhead sea turtle ( Caretta caretta ) was recently chosen by the European Commission as a bio-indicator for plastic pollution within the Mediterranean basin. We further investigated which items this key species is more prone to ingest, following the standardised Marine Strategy Framework Directive protocols. Moreover, we integrated to this protocol the Fourier Transform Infrared Spectroscopy, which allowed us to determine the polymer type of each item. We analysed samples from 226 sea turtles from 2008 to 2017 in two areas of the western Mediterranean sub-region ( sensu MSFD). In the Lazio area we found a frequency of occurrence of plastic ingestion of 78.33%, while in Sardinia 41.79%. The analysis of the litter categories, among all individuals, highlights a prevalence of user-sheet (Use-She; 69.13%) and user-fragment plastics (Use-Fra; 20.84%). In addition, the polymer analysis showed a dominance of polyethylene (65.98%) and polypropylene (26.23%). As a result, by looking at other works that have investigated polymer types and items sources, we are able to infer that 77.25% of the objects ingested by the C. caretta individuals are attributable to disposable daily-life objects managed in an improper way. Therefore, C. caretta apart from being an efficient bio-indicator for plastic pollution, highlighting spatial and temporal concentration differences, it could also be used to verify the effectiveness of the Single-use Plastic Directive (EU 2019/904). Graphical abstract: Image 1 Highlights: Different frequency of occurrence was observed between Lazio and Sardinia. Sheets and fragments were the most ingested plastic categories. Polyethylene and Polypropylene were the main plastics polymers affecting C. caretta . A 77% of single-use plastics was ingested by loggerhead turtles. We added information useful for the Single-Use Plastic Directive. Abstract : We underline the importance of aiding FT-IR analysis in assessing plastic ingestion in the bioindicator C. caretta, showing prevalence of PE and PP attributable to single-use plastics.